Candida albicans V132 induces trained immunity and enhances the responses triggered by the polybacterial vaccine MV140 for genitourinary tract infections - Martín-Cruz, Leticia; Angelina, Alba; Baydemir, Ilayda; Bulut, Özlem; Subiza, José Luis; Netea, Mihai G.; Domínguez-Andrés, Jorge; Palomares, Oscar (Frontiers in Immunology, 2022)
Recurrent urinary tract infections (RUTIs) and recurrent vulvovaginal candidiasis (RVVCs) constitute major healthcare problems with a high socio-economic impact worldwide. Antibiotics and antifungals remain the standard of care for such infectious diseases, but their overuse is associated with microbial resistances and deleterious effects on the microbiota. The development of novel approaches for genitourinary tract infections (GUTIs) such as trained immunity-based vaccines (TIbV) is therefore highly required. MV140 is a sublingual whole-cell heat-inactivated polybacterial preparation with demonstrated clinical efficacy for RUTIs. The sublingual heat-inactivated Candida albicans vaccine V132 has been developed for RVVCs. We previously showed that the combination of MV140 and V132 promotes potent Th1/Th17 and regulatory T-cell responses against antigens contained in the formulation and unrelated antigens. The specific contribution of each preparation to such effects and the underlying molecular mechanisms remain incompletely understood. Herein, we uncover that V132 induces trained immunity in human PBMCs and purified monocytes, significantly increasing the responses triggered by subsequent stimulation with MV140. Mechanistically, V132 drives metabolic rewiring towards increased glycolysis and oxidative phosphorylation and induces epigenetic reprogramming that enhances the transcription of the pro-inflammatory genes IL6 and TNFA. Peritoneal cells and splenocytes from mice immunized with V132 display enhanced responses upon in vitro stimulation with MV140. Remarkably, splenocytes from mice sublingually immunized with V132 and challenged in vivo with MV140 show significantly higher Th17 responses upon in vitro stimulation with MV140 than mice sublingually exposed to control excipients. Overall, we provide novel mechanistic insights into how V132-induced trained immunity enhances both innate and adaptive immune responses triggered by MV140, which might open the door for new interventions for GUTIs with important clinical implications.